2022
DOI: 10.1007/s15010-022-01802-1
|View full text |Cite
|
Sign up to set email alerts
|

Higher vaccination rates predict reduction in SARS-CoV-2 transmission across the United States

Abstract: Purpose The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) began proliferating widely throughout the world in late 2019/early 2020, creating a global pandemic and health crisis. Although vaccines became available to the public approximately 1 year after the onset of the pandemic, there still remains much hesitancy surrounding vaccination. One key concern comes from reports of breakthrough infections among the vaccinated that show comparable levels of peak viral load as the unvaccina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Data, updated to 24 October 2021, reported that 23 vaccines were each approved by at least one country and have been granted emergency use authorization or made available for use outside of clinical trials via any pathway by a regulatory agency, a national authority, or another entity [ 3 ]. Studies showed that vaccines contributed to the control of the COVID-19 pandemic worldwide, and may have provided a degree of herd immunity [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data, updated to 24 October 2021, reported that 23 vaccines were each approved by at least one country and have been granted emergency use authorization or made available for use outside of clinical trials via any pathway by a regulatory agency, a national authority, or another entity [ 3 ]. Studies showed that vaccines contributed to the control of the COVID-19 pandemic worldwide, and may have provided a degree of herd immunity [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many of those are in countries across the globe with only 3 focused on the United States and only 1 focusing on the general population. That study found that a “… higher proportion of fully vaccinated individuals reported fewer new cases among the remaining unvaccinated population.” 20…”
Section: Discussionmentioning
confidence: 99%
“…That study found that a " : : : higher proportion of fully vaccinated individuals reported fewer new cases among the remaining unvaccinated population." 20 In the sea of misinformation mentioned above, the public needs educated healthcare individuals, who they trust to help guide them in the choice of vaccination. Extending the front lines of vaccination to the primary care physician (PCP) could help alleviate many of the health equality concerns as well as the barriers to vaccination identified by the HBM.…”
Section: Discussionmentioning
confidence: 99%
“…Because vaccine hesitancy rates are increasing day by day, it is important to find out the main reasons for this subject. Unvaccinated persons transmit infectious diseases easily to the main population (7).…”
Section: Introductionmentioning
confidence: 99%